Guide to Web Based Digital Archive Management System: ArchivesSpace - Geday, Tekleweyni; Gebremedhin, Araya, Hibu; Birhanu, Guesh, Amiha; Kahsay, Tewelde, Tesfay (My University, 2024)
The 2020 technical manual titled Guide to Web-Based Digital Archive Management System: ArchivesSpace was collaboratively developed by researchers from Mekelle University, Ethiopia, to meet the specific needs of Tigray memory institutions in enhancing their archive and manuscript management. This manual addresses the critical need for effective digital archive management, particularly tailored to the context of Tigray, Ethiopia, and aimed at institutional memory experts. It explores the significance of archives in preserving historical materials, encompassing a wide array of media and formats, and emphasizes the cultural necessity and management responsibility associated with professional archivists. The manual also explores the current trends in archive management technology, highlighting the role of computerization and the challenges and considerations involved in automation. Furthermore, it provides insights into the ArchivesSpace open-source application, designed to facilitate the management and web access of archives, manuscripts, and digital objects. The manual offers practical guidance on utilizing ArchivesSpace, including its public and staff-side interfaces, and provides a guide to access to a sandbox for testing purposes. By addressing the customization and configuration of web-based digital archival materials, the manual aims to empower archivists, librarians, museum managers, and information center users to effectively manage archival collections, identify and access rare documents, and adhere to relevant archival standards and best practices. This manual was prepared in 2020 to address the Tigray Memory institution's demands on effective archive and manuscript management. Regrettably, the implementation of ArchivesSpace faced obstacles due to the disturbing events of the November 2, 2020, brutal war in Ethiopia. Despite these challenges, the publication of this guide aims to foster awareness and encourage the adoption of web-based digital archive management systems by memory institutions such as libraries, museums, and heritage custodians. Looking ahead, the researchers plan to extend their work by publishing an article in a peer-reviewed journal. This forthcoming article will provide recommendations to policymakers, memory institution stakeholders, researchers, and the general public, drawing from the project's findings. In essence, this comprehensive manual stands as an invaluable resource for memory institutions in Tigray, Ethiopia, underscoring the significance of effective digital archive management in preserving cultural heritage.
Supplemental materials: https://osf.io/4nyhu/
Keywords: Accession; Archive; ArchivesSpace; Digital Object; Finding aid; Memory institutions; Preservation; Tigray